Communication skills training enhances nurses' ability to respond with empathy to parents' emotions in a neonatal intensive care unit. (21st January 2016) - Bry, Kristina; Bry, Maija; Hentz, Elisabet; Karlsson, Håkan L.; Kyllönen, Hanna; Lundkvist, Malin; Wigert, Helena
Abstract: Aim: We quantitatively analysed the effect of a course in communication on the content of nurse–parent encounters and the ability of nurses to respond to the empathic needs of parents in a level III neonatal intensive care unit. Methods: We evaluated 36 and 45 nurse–parent encounters audio recorded before and after 13 neonatal nurses attended a communication course. The number of empathic opportunities, the nurses' responses to these and the ways they involved parents in their infants' care were studied. Results: Both before and after the course, the nurses talked more than the parents during the conversations. This nurse‐centredness decreased after the course. The use of empathic or exploring responses to empathic opportunities increased from 19.9 ± 9.0% to 53.8 ± 8.9% (p = 0.027), whereas ignoring the feelings of the parents or giving inadequate advice decreased from 63.0 ± 10.0% to 27.5 ± 8.4% (p = 0.043) after the course. Use of statements expressing caring for the parents and encouragement for parents to participate in the care of their infant increased after the course (p = 0.0034 and p = 0.043, respectively). The nurses felt the course was very useful for their profession. Conclusion: A course in communication techniques improved nurses' ability to respond to parents' feelings with empathy.